Migraine as a Risk Factor for Stroke - Vinall, Phil (MD Conference Express, 2011)
The following summary discusses several presentations concerning the relationship between migraines and stroke, including epidemiology, genetics, and mechanisms, in an effort to explain the link between migraines with aura and stroke.